Thymus in children with type 1 diabetes mellitus - Olga Borisovna Sirotina (Endocrinology Research Centre, 2011)
Aim. To determine size structure and blood circulation of thymus in children with type 1 diabetes mellitus (DM1) by ultrasound.We have undertaken an ultrasonic study of thymus in 62 children aged 4-17 years with DM1 to determine its size, structure and bloodcirculation. Results.It was shown for the first time that the thymus of DM1 children is enlarged and fairly well visualized unlike that in agematchedhealthy patients in whom it is much smaller due to age-related involution and substitution of the thymic tissue by adipose one. Colorand energetic Doppler mapping showed perfect vascularization of the thymus in DM1 children compared with healthy patients in whom thismethod failed to map blood flow due to the substitution of the original thymic tissue by parenchymal and adipose tissues and dropout of bloodvessels. Conclusion the study for the first time gave evidence that thymus, the main immunogenic organ (conductor of the immune system),undergoes age-specific changes of size and structure whereas DM1 of autoimmune etiology precludes its involution.